Locus coeruleus at asymptomatic early and middle Braak stages of neurofibrillary tangle pathology. (19th April 2017) - Andrés‐Benito, P.; Fernández‐Dueñas, V.; Carmona, M.; Escobar, L. A.; Torrejón‐Escribano, B.; Aso, E.; Ciruela, F.; Ferrer, I.
Abstract : Aims: The present study analyses molecular characteristics of the locus coeruleus (LC) and projections to the amygdala and hippocampus at asymptomatic early and middle Braak stages of neurofibrillary tangle (NFT) pathology. Methods: Immunohistochemistry, whole‐transcriptome arrays and RT‐qPCR in LC and western blotting in hippocampus and amygdala in a cohort of asymptomatic individuals at stages I–IV of NFT pathology were used. Results: NFTs in the LC increased in parallel with colocalized expression of tau kinases, increased neuroketal adducts and decreased superoxide dismutase 1 in neurons with hyperphosphorylated tau and decreased voltage‐dependent anion channel in neurons containing truncated tau were found. These were accompanied by increased microglia and AIF1, CD68, PTGS2, IL1 β, IL6 and TNF‐ α gene expression. Whole‐transcriptome arrays revealed upregulation of genes coding for proteins associated with heat shock protein binding and genes associated with ATP metabolism and downregulation of genes coding for DNA‐binding proteins and members of the small nucleolar RNAs family, at stage IV when compared with stage I. Tyrosine hydroxylase (TH) immunoreactivity was preserved in neurons of the LC, but decreased TH and increased α2A adrenergic receptor protein levels were found in the hippocampus and the amygdala. Conclusions: Complex alteration of several metabolic pathways occurs in the LC accompanying NFT formation at early and middle asymptomatic stages of NFT pathology. Dopaminergic/noradrenergic denervation and increased expression of α2A adrenergic receptor in the hippocampus and amygdala occur at first stage of NFT pathology, suggesting compensatory activation in the face of decreased adrenergic input occurring before clinical evidence of cognitive impairment and depression. Abstract : Novel alterations in metabolic pathways in the locus coeruleus accompany tau pathology in pre‐symptomatic Alzheimer's disease have implications for disease mechanisms and developing treatment strategies.